Heritage Heboh - An Alternative Educational Success Story - Caroline Marshall (Wacana Seni Journal of Arts Discourse, 2006)
The words "learning" and "excitement" don't generally go together when it refers to education in Malaysia. Even less do we find learning that happens with the students taking the initiative. Learning history facts without having to be force fed? Are you kidding? Making inquiries and doing further research without being asked so that they can better understand and look for answers to their individual questions? A MULTI-RACIAL group of students EXCITED about working together?